Securitization (and de-securitization) of the European refugee crisis - Jakešević, Ružica (Teorija in praksa, 2016)
The aim of this paper is to analyse the refugee crisis in South-East Europe in 2015/2016 in the context of the securitization theory which was defined by prominent representatives of the Copenhagen school of security studies: Barry Buzan, Ole Waver and Jaap De Wilde. The analysis will focus on the Republic of Croatia and its immediate surroundings, and will look into relevant parameters in order to determine whether the securitization of this phenomenon was successful. The securitization of the recent refugee crisis can be observed at micro and macro levels. At the macro level, the analysis will tackle the EU response as well as shortcomings in the common EU migration and asylum policy and the disagreement of member states with methods for solving this crisis. At the micro level, the influence of the refugee crisis can be viewed from two perspectives: from the perspective of different domestic actors which are using the refugee crisis as a tool for political mobilisation, and from the perspective of the influence on interstate relations. However, we can observe actors inclined towards securitization and those inclined towards de-securitization at both levels.
Keywords: Begunci; begunska kriza; Croatia; Hrvaška; jugovzhodna Evropa; Nacionalna varnost; National security; Refugees